Identification of Giardia lamblia Genotypes among Children in Tikrit City by Using Nested PCR (Indian Journal of Forensic Medicine & Toxicology, 2021)
The parasite Giardia lamblia is one of the most widespread intestinal protozoa that infects humans allover the world, causing giardiasis. It was first diagnosed in the duodenum and ileum in human digestivetract, where its effect is primarily on children. Giardia disease affects more than 280 million people everyyear worldwide. It is also one of the most important parasitic infections in many countries in terms ofincidence and morbidity. 615 stool samples were collected from children attending Tikrit Teaching Hospitaland private laboratories during the study pehriod to investigate the spread of G. lamblia among children, andthe total infection rate was 14.30%. Where the rate of infecting children in the city was 11.54% of the totalof 50 samples. Through the molecular examination in this study, the parasite G. lamblia, the target gene TPItriose phosphate isomerase was used to identify clusters of G. lamblia. All positive samples were positivewith group B and no infection was registered with group A.
Keywords: parasites, Giardia lamblia, Giardiasis, Nested PCR.